#TITLE_ALTERNATIVE# - ADITYA PUSPA KANIA (NIM 10107082); Pembimbing : Prof. Dr. Edy Tri Baskoro, Ph. D. dan Drs. War, RISKA
In angklung's performances, we must determine how to distribute angklung so that every performer doesn't play any two or more angklung in the same time. This problem is solved by a method called tonjur. Tonjur's method gives us information about how much an angklung be played in that song and the compatible pairs of each angklung's number. The result of tonjur is used to decide angklung distribution. The song which played be modeled as a graph, where a vertex is an angklung's number and an edge defined as an overlapping between two angklung's number. The compatible pairs of every angklung are known by its adjacency matrix. Distribution of angklung to performer being solved by applied vertex colouring method to a graph. The minimal number of colour that used for colouring a graph represents the minimal number of performer in a performances. If the number of avaliable performer less than the minimal number of performer, then the set of angklung which haven't been assigned to any performer have must to distributed to avaliable performer so that the total weight of overlapping of that distribution is minimal. The solution of that problem is obtained by using heuristic method.